Creativity and Innovation in Indonesia’s Digital Entrepreneurship: Insight from Content Creators and Start-ups - Mariah, Mariah; Hernawan, Hernawan (International Journal of Social Science and Business, 2025)
This study investigates the intertwined roles of creativity and innovation in shaping digital entrepreneurship among content creators and local start-ups in Indonesia. Employing a qualitative, exploratory case study approach, the research draws insights from in-depth interviews, observations, and document analysis of five entrepreneurs operating across diverse sectors, including education, fashion, food, agriculture, and technology. The findings reveal that creativity functions as the initial driver of entrepreneurial activity, serving not only as a spark for idea generation but also as a continuous process of experimentation and adaptation to evolving consumer preferences and technological advancements. Innovation, on the other hand, emerges as an adaptive mechanism through which creative ideas are transformed into marketable products, services, and sustainable business models. Digital platforms such as Instagram, TikTok, and YouTube act as crucial enablers, lowering entry barriers, broadening market access, and fostering collaborative ecosystems. However, the study also identifies persistent challenges, including limited managerial capacity, scarce resources, and difficulties in sustaining brand consistency. Furthermore, cultural and social dynamics are found to significantly influence entrepreneurial practices, shaping strategies for creativity, innovation, and audience engagement. By highlighting the gap between individual creativity and structured innovation management, this study emphasizes the importance of systematic approaches to ensure sustainability and scalability of digital ventures. Overall, the research contributes to the literature on digital entrepreneurship by integrating perspectives on creativity, innovation, and cultural context, offering practical implications for policymakers, educators, and ecosystem builders seeking to strengthen Indonesia’s rapidly evolving digital economy.